Draft Genome Sequence of the Methicillin-Resistant Staphylococcus aureus Isolate MRSA-M2 - Harro, Janette M. (American Society for Microbiology, 2013)
We report the draft genome sequence of a methicillin-resistant strain of Staphylococcus aureus, designated MRSA-M2. This clinical isolate was obtained from an osteomyelitis patient undergoing treatment at the University of Texas Medical Branch (Galveston, TX). This strain is an ST30, spa type T019, agr III strain and has been utilized as a model S. aureus strain in a number of proteomic, transcriptomic, and animal model studies.